Blockchain sebagai Pilar Keamanan IoT: Tinjauan Sistematis tentang Mekanisme Otentikasi dan Integritas Data - Nur Sa'diah Nasution; Adelia Mestika Kusuma W; Bela Sukma Yani; Indah Oktavia Ramadhani; May Utami; Mucklas Arya Qodri; Nurul Annisa (Pusat Riset dan Inovasi Nasional, 2026)
This study explores the significance of Blockchain technology in bolstering the security of Internet of Things (IoT) systems, particularly concerning authentication and data integrity mechanisms. Utilizing a systematic literature review (SLR) approach, the research involves formulating research questions, performing extensive literature searches, setting inclusion and exclusion criteria, selecting pertinent studies, and processing and analyzing the data to draw conclusions. The findings indicate that Blockchain considerably enhances IoT security by offering robust authentication techniques that ensure only authorized devices gain network access, in addition to improving data integrity through unalterable transaction records. Furthermore, the decentralized nature of Blockchain reduces single points of failure and increases system resilience against cyberattacks. These results highlight Blockchain's potential to address security weaknesses within IoT frameworks. In summary, this research emphasizes the critical role of Blockchain in securing IoT ecosystems and building trust among users and stakeholders. Future investigations should aim to tackle scalability and interoperability issues, as well as evaluate real-world implementations, to maximize the effectiveness of Blockchain in IoT security.